Republic of Congo : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative; Preliminary Document. (IMF Staff Country Reports; Country Report, 2005)
This paper reviews the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative of the Republic of Congo. Emerging from a conflict situation, and starting from a low base, Congo has made significant progress in implementing financial and structural reforms, but large challenges remain. The overall improving political and security conditions allowed the authorities to make good progress toward restoring macroeconomic and financial stability. Debt relief under the enhanced HIPC Initiative would reduce Congo's external debt by nearly one-half.